Balloon aortic valvuloplasty to improve candidacy of patients evaluated for transcatheter aortic valve replacement. (28th December 2017) - Arsalan, Mani; Khan, Samir; Golman, Jake; Szerlip, Molly; Mahoney, Cecile; Herbert, Morley; Brown, David; Mack, Michael; Holper, Elizabeth M.
Abstract : Objectives: Evaluate the role of balloon aortic valvuloplasty (BAV) in improving candidacy of patients for transcatheter aortic valve replacement (TAVR). Background: Patients who are not candidates for TAVR may undergo BAV to improve functional and clinical status. Methods: 117 inoperable or high‐risk patients with critical aortic stenosis underwent BAV as a bridge‐to‐decision for TAVR. Frailty measures including gait speed, serum albumin, hand grip, activities of daily living (ADL); and NYHA functional class before and after BAV were compared. Results: Mean age was 81.6 ± 8.5 years and the mean Society of Thoracic Surgeons predicted risk of mortality was 9.57 ± 5.51, with 19/117 (16.2%) patients non‐ambulatory. There was no significant change in mean GS post‐BAV, but all non‐ambulatory patients completed GS testing at follow‐up. Albumin and hand grip did not change after BAV, but there was a significant improvement in mean ADL score (4.85 ± 1.41 baseline to 5.20 ± 1.17, P  = 0.021). The number of patients with Class IV congestive heart failure (CHF) was significantly lower post BAV (71/117 [60.7%] baseline versus 18/117 [15.4%], P  = 0.008). 78/117 (66.7%) of patients were referred to definitive valve therapy after BAV. Conclusions: When evaluating frailty measures post BAV, we saw no significant improvement in mean GS, however, we observed a significant improvement in non‐ambulatory patients and ADL scores. We also describe improved Class IV CHF symptoms. With this improved health status, the majority of patients underwent subsequent valve therapy, demonstrating that BAV may improve candidacy of patients for TAVR.